Discrimination of Dendropanax morbifera via HPLC fingerprinting and SNP analysis and its impact on obesity by modulating adipogenesis- and thermogenesis-related genes - Awais, Muhammad; Akter, Reshmi; Boopathi, Vinothini; Ahn, Jong Chan; Lee, Jung Hyeok; Mathiyalagan, Ramya; Kwak, Gi-Young; Rauf, Mamoona; Yang, Deok Chun; Lee, Geun Sik; Kim, Yeon-Ju; Jung, Seok-Kyu (Frontiers in Nutrition, 2023)
Dendropanax morbifera (DM), a medicinal plant, is rich in polyphenols and commonly used to treat cancer, inflammation, and thrombosis. However, till date, no study has been conducted on DM regarding the enormous drift of secondary metabolites of plant in different regions of Republic of Korea and their effects on antiobesity, to explore compounds that play an important role in two major obesity-related pathways. Here, we present an in-depth study on DM samples collected from three regions of Republic of Korea [Jeju Island (DMJ), Bogildo (DMB), and Jangheung (DMJG)]. We used high-performance liquid chromatography (HPLC) and multivariate component analyses to analyze polyphenol contents (neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, and rutin), followed by discrimination of the samples in DMJG using single nucleotide polymorphism and chemometric analysis. In silico and in vitro evaluation of major compounds found in the plant extract on two major anti-obesity pathways (adipogenesis and thermogenesis) was carried out. Furthermore, comparing parallelly with seventeen experimental runs, two extraction methods (Soxhlet and ultrasound-assisted extraction) were used to understand which method is better and why. Upon quantifying three regions with the polyphenols, DMJG had the highest content of polyphenols. The internal transcribed region (ITS) region revealed a specific gel-based band for the authentication of DMJG. PCA and PLS-DA revealed the polyphenol’s discriminative power of the region DMJG. The anti-obesity effects of plant extracts from the three regions were related to their polyphenol contents, with DMJG showing the highest effect followed by DMJ and DMB. Ultrasound-assisted extraction yielded a high amount of polyphenols compared to that by the Soxhlet method, which was supported by scanning electron microscopy. The present work encourages studies on plants rich in secondary metabolites, to efficiently use them for dietary and therapeutic purposes.